2007
DOI: 10.1002/pat.894
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porphyrins bearing uracyl groups and their assembly induced by melamine derivatives

Abstract: Self-assembled porphyrins via noncovalent bonding have attracted wide-ranging researchers in material science. We reported herein the synthesis of the tetraphenyl porphyrin derivatives bearing uracyl groups as acceptor-donor-acceptor (ADA) type hydrogen bonding units, through the condensation of 5,10-or 5,15-bis (3-amino-4-ethylhexylphenyl) porphyrin derivatives with 6-carboxyuracyl derivatives. When two porphyrins having uracyl groups at the different substituted positions were respectively mixed with a melam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For instance, the uracil-functionalized porphyrins described by Drain et al, [14] the water-soluble NB-porphyrins reported by Maiya et al [15] and the NB-porphyrin hybrid compounds described by Schneider et al [16] were synthesized by an Adler synthesis, [17] alkylation reactions of NB's active amine sites and by a condensation reaction between corresponding NBs and porphyrin derivatives respectively. Furthermore, the synthesis of porphyrins bearing nucleobases via ethoxy and acetyl linkers [18] or via amide linkers [19] was also reported. Taking into consideration the previously followed synthetic pathways, we developed two new simple approaches to synthesize NB-porphyrins architectures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the uracil-functionalized porphyrins described by Drain et al, [14] the water-soluble NB-porphyrins reported by Maiya et al [15] and the NB-porphyrin hybrid compounds described by Schneider et al [16] were synthesized by an Adler synthesis, [17] alkylation reactions of NB's active amine sites and by a condensation reaction between corresponding NBs and porphyrin derivatives respectively. Furthermore, the synthesis of porphyrins bearing nucleobases via ethoxy and acetyl linkers [18] or via amide linkers [19] was also reported. Taking into consideration the previously followed synthetic pathways, we developed two new simple approaches to synthesize NB-porphyrins architectures.…”
Section: Introductionmentioning
confidence: 99%